Aves pampeanas: El desafío de salvar la fauna del pastizal - López-Lanús, Bernabé; Marino, Gustavo; D'Alessio, Santiago (Revista Aves Argentinas, 2012)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).